Embryonic death as a probable reason for the collapse of population densities in Lymantria dispar (Linnaeus, 1758) (Lepidoptera: Erebidae, Lymantriinae) - A. Ilyinykh; I. Dubovskiy; O. Polenogova; V. Ponomarev; V. Glupov (SHILAP, 2024)
For the first time the causes of mass death of embryos in a population of Lymantria dispar (Linnaeus, 1758) with biochemical and molecular methods are investigated. In this study egg masses were collected in the territory of Russia from two populations, with low (the West Siberian population) and high (Trans-Ural) density and analyzed. Spring hatching of larvae from the eggs stored under constant laboratory conditions at 2º C was two times lower for insects of the Trans-Ural (TU) population compared to the West Siberian (WS) population (43 ± 6 % and 86 ± 7 % accordingly). The level of virus defined by PCR for TU and WS populations was 76±9 % and 36±6%, respectively. The major components of eggs were the same between populations. However, we found decreased concentrations of proteins important for embryogenesis in TU population, such as an arilforin-like molecule and no vitellin 2-like component. Field data were comparable to those of the laboratory, and in TU populations there was a decrease of density. The obtained results suggest that alteration in hormonal balance of the infected with nucleopolyhedrovirus (NPV) insects may lead to a decrease or absence of some key proteins of embryogenesis in eggs. It can influence hatching of larvae from eggs and, accordingly, population dynamics of the lepidopteran.